Calcium distribution in Amoeba proteus (The Rockefeller University Press, 1979)
A preliminary investigation of the distribution of cellular calcium in Amoeba proteus was undertaken. Total cellular calcium under control conditions was found to be 4.59 mmol/kg of cells. When the external Ca++ concentration is increased from the control level of 0.03 to 20 mM, a net Ca++ influx results with a new steady-state cellular calcium level being achieved in integral of 3 h. At steady state the amount of calcium per unit weight of cells is higher than the amount of calcium per unit weight of external solution when the external concentration of Ca++ is below 10 mM. At external Ca++ concentrations above this level, total cellular calcium approaches the medium level of Ca++. Steady- state calcium exchange in Amoeba proteus was determined with 45Ca. There is an immediate and rapid exchange of integral of 0.84 mmol/kg of cells or 18% of the total cellular calcium with the labelled Ca++. Following this initial exchange, there was very little if any further exchange observed. Most of this exchanged calcium could be eliminated from the cell with 1 mM La+++, suggesting that the exchanged calcium is associated with the surface of the cell. Increase in either the external Ca++ concentration of pH raise the amount of exchangeable calcium associated with the cell. Calcium may be associated with the cell surface as a co-ion in the diffuse double layer or bound to fixed negative sites on the surface of the cell. If Ca++-binding sites do exist on the cell surface, there may be more than one type and they may have different dissociation constants. The cytoplasmic Ca++ ion activity is probably maintained at very low levels.